2001
DOI: 10.1097/00000658-200104000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Reticuloendothelial System Blockade Promotes Progression from Mild to Severe Acute Pancreatitis in the Opossum

Abstract: ObjectiveTo examine the relation between hepatic reticuloendothelial system (RES) dysfunction and the development of acute biliary pancreatitis. In an opossum model, the authors tested the hypothesis that RES blockade can turn the mild pancreatitis seen after pancreatic duct obstruction (PDO) into the severe form. Summary Background DataBiliary obstruction is considered the decisive event in gallstone pancreatitis. Suppression of the RES occurs during biliary obstruction. MethodsEighteen opossums were placed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…(a) Bile duct ligation alone is known to raise circulating cholecystokinin levels in the blood and could, by itself, exert a stimulatory effect on the pancreas (14). (b) It has been suggested that bile duct obstruction could be a confounding or aggravating factor for the events involved pancreatic duct obstruction-induced pancreatitis (15,16). (c) Ligation of the pancreatic duct system in mice without compromising the unimpaired flow of bile is technically more prone to surgical complications than ligation of both ducts and the latter is a more likely to reflect the situation that arises when a gallstone is impacted at the papilla.…”
Section: Methodsmentioning
confidence: 99%
“…(a) Bile duct ligation alone is known to raise circulating cholecystokinin levels in the blood and could, by itself, exert a stimulatory effect on the pancreas (14). (b) It has been suggested that bile duct obstruction could be a confounding or aggravating factor for the events involved pancreatic duct obstruction-induced pancreatitis (15,16). (c) Ligation of the pancreatic duct system in mice without compromising the unimpaired flow of bile is technically more prone to surgical complications than ligation of both ducts and the latter is a more likely to reflect the situation that arises when a gallstone is impacted at the papilla.…”
Section: Methodsmentioning
confidence: 99%
“…In gallstone pancreatitis, stone impaction may occur either at the choledochoduodenal junction below the confluence of the biliary and pancreatic ducts, which produces a common channel, or at the confluence of the biliary and pancreatic ducts, which produces obstruction of both ducts. The common channel theory proposed by Opie24 has been challenged by the observation that pancreatic duct pressure exceeds biliary duct pressure, suggesting that, even if a common channel existed, reflux of pancreatic juice into the biliary duct, rather than flow of bile into the pancreas would be expected 29. Fumino et al30 showed clinical evidence of two‐way regurgitation: pancreaticobiliary reflux (PBR) and biliopancreatic reflux (BPR), in patients with anomalous arrangements of the pancreaticobiliary ducts (AAPBD).…”
Section: Discussionmentioning
confidence: 97%
“…They also noted that abdominal pain with hyperamylasemia was significantly more frequent in patients with PBR than in patients with BPR, and hypothesized that hyperamylasemia in patients with AAPBD is caused by cholangiovenous reflux. Today, most authors disagree with the common channel theory proposed by Opie 29…”
Section: Discussionmentioning
confidence: 99%
“…CAR is preferentially incorporated by the Kupffer cells in the liver [36]. Administration of CAR to animals also creates an experimental model of jaundice [37].…”
Section: Discussionmentioning
confidence: 99%